Oral Hygiene and Dental Caries Status on Systemic Lupus Erythematosus Patients: A Cross-Sectional Study - Nanda Rachmad Putra Gofur; Kusworini Handono; Nurdiana Nurdiana; Handono Kalim; Wisnu Barlianto (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the oral hygiene and dental caries status on Systemic Lupus Erythematosus (SLE) patients, also it's with SLE disease activity. Material and Methods: This is a descriptive study with a cross-sectional approach. The study was conducted on 93 SLE patients from 2017 to 2019 on Saiful Anwar Hospital Indonesia. All SLE patients had clinical examination using DMF-T, Personal Hygiene Performance-Modified (PHP-M), Calculus Index (CI), Debris Index (DI), Plaque Index (PI) and Simplified Oral Hygiene Index (OHI-S). Clinical examination and laboratory tests are conducted to assess the activity of SLE measured using. The data were analyzed by One Way ANOVA test. Results: A total of 74% of subjects with SLE had dental caries. PHP-M with SLE severity was found significant (p<0.001) and a strong positive correlation (r=0.982). Plaque with SLE severity was found significant (p=0.001) and a strong positive correlation (r=0.938). OHI-S with SLE severity was found significant (p<0.001) and a strong positive correlation (r=0.953). DMF-T levels with SLE severity was found significant (p=0.001) and a strong positive correlation (r=0.974). It showed that the severity of disease activity was related to poor oral hygiene and a high incidence of dental caries. Conclusion: There is a correlation between oral hygiene, dental caries and SLE severity.